2015
DOI: 10.1007/s12011-015-0357-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in Gastrointestinal Tract Tissues Induced by Arsenic Toxicity in Cocks

Abstract: Arsenic (As) is a widely distributed trace element which is known to be associated with numerous adverse effects on human beings and animals. Arsenic trioxide (As2O3) is an inorganic arsenical-containing toxic compound. The effect of excessive amounts of As2O3 exposure on gastrointestinal tract tissue damage in cocks is still unknown. This study was conducted to investigate the effect of As2O3 exposure on gastrointestinal tract tissue damage in cocks. In total, 72 1-day-old male Hyline cocks were randomly divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 31 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Heavy metals exposure thus is linked to intestinal microbiota dysbiosis, whereas the distinction of intestinal microbiota might contribute to the species and dose of heavy metals. Previous studies have demonstrated that the heavy metal species has a specific effect on the transport, oxidative, and inflammatory status of the gut epithelium (Breton et al, 2013b;Guo et al, 2015). Interestingly, different types of dysbiosis are likely related to various diseases, including inside and outside the intestine.…”
Section: Effect Of Heavy Metals On Intestinal Microbiotamentioning
confidence: 99%
“…Heavy metals exposure thus is linked to intestinal microbiota dysbiosis, whereas the distinction of intestinal microbiota might contribute to the species and dose of heavy metals. Previous studies have demonstrated that the heavy metal species has a specific effect on the transport, oxidative, and inflammatory status of the gut epithelium (Breton et al, 2013b;Guo et al, 2015). Interestingly, different types of dysbiosis are likely related to various diseases, including inside and outside the intestine.…”
Section: Effect Of Heavy Metals On Intestinal Microbiotamentioning
confidence: 99%
“…In this study, we investigated the effects of long term exposure and withdrawal of NaAsO 2 on the liver and erythrocyte. It was well established that arsenic causes toxicity by the process of oxidative stress [37] , [38] , [39] , [40] . Also, reactive oxygen and nitrogen species (ROS, RNS) are generated and are due to the presence of unpaired electrons in their outer orbit that ultimately make them extremely reactive [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic increases the free reactive oxidation species and causes oxidative stress and damage to the epithelial cells in the GIT [35]. The intestines have a large mucosal layer surface lined with epithelial cells, protecting the body from entry of toxic chemicals and harmful bacteria into the systemic circulation, while being selectively permeable to limited chemicals, water and nutrients.…”
Section: Introductionmentioning
confidence: 99%